يثرب المدينة قبل الإسلام - إبراهيم، إسراء إبراهيم بكري (مركز بحوث ودراسات دول حوض البحر الأحمر والاتحاد الدولي للمؤرخين, 2020)
تهدف هذه الدراسة إلى إلقاء الضوء على تاريخ يثرب قبل الإسلام. وتتمثل مشكلة الدراسة في أن تاريخ يثرب المدينة كان غامضا ومجهولا رغم أن يثرب لها من الخصائص والمميزات الحضارية قبل الإسلام ما أهلها لتكون حاضنة الدولة الإسلامية وبؤرة إشعاع إسلامي لاحقا. وتكمن أهميتها في إماطتها اللثام عن تاريخ يثرب الذي كان مجهولا وغامضا، اتبعت الدراسة المنهج التاريخي الوصفي التحليلي بغية الوصول إلى نتائج علمية ولعل أهم ما توصلت إلية الدراسة من نتائج معرفة تاريخ يثرب وما له وما عليه قبل الإسلام والتنوع السكاني والديني والحضاري في يثرب قبل الإسلام، كما أوصت الدراسة بضرورة إجراء المزيد من البحوث حول تاريخ يثرب قبل الإسلام لاكتشاف المزيد من المعلومات التاريخية الأثرية عن تلك المدينة التي أصبحت من أهم وأكبر المدن بعد مكة المكرمة.
The study aims at shedding light on the history of Yathrib (the ancient name for Medina) before the advent of Islam. Though the city of Yathrib, before Islam, had what it took to serve as a seedbed for the Islamic State and the home of Islam afterwards, very little is known about its history. The study’s significance lies in its potential to uncover the history of Yathrib, which was shrouded in mystery. To achieve its purpose, the study has adopted the historical descriptive-analytical approach. The most salient findings to emerge from the current study are: identifying Yathrib’s history and its status before the advent of Islam, and the demographic, religious and cultural diversity in Yathrib in the pre-Islamic era. The study recommends that more research needs to be done on this area to unearth further archaeo-historical information about Yathrib, which has become the largest and most important city other than Mecca.
Keywords: التاريخ الإسلامي -- الحضارة الإسلامية -- المعالم التاريخية الإسلامية -- المدينة المنورة(يثرب) -- السعودية